Daughter of Chorolque - Park, Mi-Sun (Mi-sun Park, 2007)
Verzio FF Submission In the mountain desert of the Bolivian Andes female emancipation has a particular form and history. In the village of Chorolque (5,600m above sea level) the main way of earning a living is to work in tin mines, demanding work which gives women the chance to have the same status as men, feed families abandoned by husbands, or at least be able to afford a treat. A mother and daughter work together in the mine, and although they are under no illusions regarding the dangers of the miner's life, they come to terms with the reality that surrounds them thanks to their energy and mutual support. This film focuses on the strong stories of heroines who have managed even without men to provide their children with dignified living conditions by taking on tough "men's" work.